Liver-derived ketone bodies are necessary for food anticipation - Rohit Chavan (Nature Portfolio, 2016)
Food anticipation is thought to be initiated by the central clock in the brain. Here the authors show that the peripheral organs initiate this process by showing that liver-specific deletion of Per2 can inhibit food anticipation by interfering with ß-hydroxybutyrate production and its subsequent processing in the brain.